A rare nonsyndromic case of adenomatoid odontogenic tumor associated with multiple impacted supernumerary teeth - Mohanty, Rajat (Natl J Maxillofac Surg, 2019)
Adenomatoid odontogenic tumour (AOT) is a rare benign odontogenic tumour characterized by a progressively slow growing pattern and symptomless behavior. The differential diagnosis between AOT and other odontogenic tumours, such as ameloblastoma, should be well conducted in order to avoid extensive ablative surgery. The present case report is of a 27 year old female who reported with a chief complaint of mild intermittent pain and a swelling which was gradually increasing in size, on the left mid-facial region since 6 months. Radiographic Investigations revealed a round uni-locular radiolucent image of an intra-osseous lesion with a well defined border in the left maxilla. The tumor was encapsulated and was attached with 2 impacted supernumerary teeth which were fused and shaped as maxillary premolars. The images also showed multiple impacted supernumerary teeth in the maxilla and mandible. The clinical and radiographic diagnostic hypothesis of Adenomatoid odontogenic cyst and a differential diagnosis of Dentigerous Cyst was given. Surgical enucleation of the lesion was done under General Anaethesia. The histological sections were consistent with AOT.